2017
DOI: 10.17736/ijope.2017.jc702
|View full text |Cite
|
Sign up to set email alerts
|

Drilling-Induced Riser Vibration

Abstract: Significant riser oscillations were observed during deep-water drilling operations. The riser vibrated at frequencies from below to above the rotation speed of the drill pipe. Laboratory tests of a riser section have been conducted for these riser drilling-induced vibrations. The first test consisted of measuring the fluid forces between the rotating drill pipe and the riser. In the second test, the riser was elastically supported. The riser self-excited about the rotating drill pipe. An analytical model is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The resulting motion trajectories and animations for points (1), (2), and (3) under different WOB conditions are presented in Figures 4 and 5. It is worth noting that for the purpose of comparing and analyzing the movement trajectory of the drillstring (1) under different conditions, the initial static state inner diameter of the riser is utilized as a reference for sizing the circle in the displacement diagram of drillstring (1). In practical drilling operations, it is typically observed that the displacement at the middle section of the drillstring below the mud line is most significant.…”
Section: Influence Of Wobmentioning
confidence: 99%
See 2 more Smart Citations
“…The resulting motion trajectories and animations for points (1), (2), and (3) under different WOB conditions are presented in Figures 4 and 5. It is worth noting that for the purpose of comparing and analyzing the movement trajectory of the drillstring (1) under different conditions, the initial static state inner diameter of the riser is utilized as a reference for sizing the circle in the displacement diagram of drillstring (1). In practical drilling operations, it is typically observed that the displacement at the middle section of the drillstring below the mud line is most significant.…”
Section: Influence Of Wobmentioning
confidence: 99%
“…Deep-water drilling risers will have a significant impact on drillstring vibration [1,2], which is a crucial factor affecting drilling efficiency. The high levels of shock and vibration experienced during deep water drilling in Brazil [3][4][5] and Mexico [6][7][8] have severely affected the rate of penetration (ROP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded the PIP guide spring model can be used for riser design in lieu of the PIP guide surface model. Blevins [29] conducted laboratory tests for a riser with drilling-induced vibrations, which revealed that fluid dynamic coupling can cause vibration of a riser with a rotating drill pipe and a water-filled annulus.…”
Section: Introductionmentioning
confidence: 99%
“…The rod string dynamics in petroleum engineering had been studied extensively by many experts and scholars: the longitudinal vibration of sucker rod [13,14], the transverse vibration of traditional pressure bar [15,16] and moving beam [17,18], the transverse forced vibration of riser under tension [19][20][21], the transverse vibration and collision problems for wellbore under fluctuating pressure [22][23][24][25]. However, the research on the transverse vibration triggered by the buckling deformation excitation seems to have not been discovered so far.…”
Section: Introductionmentioning
confidence: 99%